(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Individuals may commit cyberbullying actions (insult, slander, etc.) to the other party, especially by using technological communication tools (phone, blogs, etc.). It is very important to be conscious of these cyberbullying acts. Therefore, the aim of this study is to investigate the strategies of university students studying in sports sciences to cope with cyberbullying. The universe of this research consists of university students studying at the faculties of sports sciences. The sample group consists of 200 students studying at Dokuz Eylül University Necat Hepkon Faculty of Sports Sciences. Stratified random sampling, one of the random sampling methods, was used. The “Coping with Virtual Bullying Scale” developed by Koç et al., (2016) was used as a data collection tool. SPSS 28.0 program was used in the analysis of the data. Kolmogorov-Smirnov and Shapiro Wilk test was used to determine the normality of the obtained data, and Independent T-Test was used to compare the variables. In the findings; A significant difference was found between male and female students in the sub-dimensions of Cognitive Security, Help-Seeking and Information-Seeking (p0.05). The significant difference in the sub-dimensions is in favor of female students. A high level of significant difference was found among students' daily internet use in the sub-dimensions of Help Seeking and Information Seeking (p0.05). The significant difference in the sub-dimensions is in favor of students who use the internet for 5 hours or more. In the Ignoring sub-dimension, there was a significant difference according to the number of social media accounts (p0.05). The significant difference is in favor of students who have 2 or more social media accounts. In the sub-dimensions of Help Seeking, Ignoring and Information Seeking, a significant difference was found between keeping social media identity confidential (p0.05). In all dimensions where a significant difference occurred (Help Seeking 18.8±3.90, Ignoring 14.0±3.25, Information Seeking 22.7±1.00) the average was in favor of students who kept their social media accounts private. As a result; It is recommended that social and academic studies be carried out to increase awareness of cyberbullying, especially among young people.